The movement of stars - Brill, Amy (Riverhead Books, a member of Penguin Group (USA), Inc., 2014)
Amateur astronomer Hannah Gardner Price has lived all twenty-four years of her life according to the principles of the Nantucket Quaker community in which she was raised. Then she meets Isaac Martin, a young, dark-skinned whaler from the Azores who, like herself, has ambitions beyond his expected station in life. Drawn to his intellectual curiosity and honest manner, Hannah agrees to take Isaac on as a student. But when their shared interest in the stars develops into something deeper, Hannah's standing in the community begins to unravel.